THE USE OF THE DEMONSTRATION METHOD TO ENHANCE PRIMARY SCHOOL STUDENTS' ABILITY IN RECITING POETRY - Suparsa, I Nyoman; Bagus Nyoman Mantra, Ida (International Journal of Multidisciplinary Reseach, 2026)
The purpose of this classroom action study was to investigate the challenges sixth-grade students of Elementary School, had when performing poetry. The study sought to determine whether the demonstration technique could help students become more proficient at reciting poetry and what actions needed to be taken in the classroom to help students become more proficient. Two cycles of the study were conducted, each of which followed the same steps. Performance-based testing and observation were used to gather data. Pre-cycle results revealed low starting performance: 5 students (13.89%) received a score of 6, 17 students (47.22%) received a score of 5, and 14 students (38.89%) received a score of 4. With 11 students (30.55%) scoring 7, 20 students (55.56%) scoring 6, and 5 students (13.89%) earning 5, Cycle I showed improvement. With 24 students (66.67%) receiving a score of 10, 6 students (16.67%) receiving a score of 9, and 5 students (13.89%) receiving a score of 8, significant progress was made in Cycle II. The trial was ended since Cycle II satisfied the predefined success criteria. The results show that the demonstration approach successfully enhances students' ability to recite poetry and encourages active learning.